DNA extraction comparisons between fresh and boiled Atlantic Salmon (S. salar) tissues. - Bernal, Victoria (Linköpings universitet, Institutionen för fysik, kemi och biologi, 2019)
Barcode identification is a method that uses genetic information to differentiate species. Because of its general versatility it can be applied to contexts from archaeology to the food industry. Atlantic salmon (Salmo salar) is a fish species commonly hunted in modern times and has been found in archaeological settings. However, barcoding requires enough quality DNA for amplification and abiotic exposure tends to degrade it. High temperatures, such as when boiling, can diminish DNA quality. The extent of DNA degradation between fresh and boiled tissues and whether all tissues retain the same amount of DNA is unclear. In this study DNA was extracted from S. salar tissues fins, muscle, bones and scales without treatment and with boiling treatment. DNA concentrations between fresh and boiled bones were not significantly different, nor were comparisons between samples with the same treatments. Muscles had higher DNA concentrations when boiled and fins had higher when fresh. These findings show that regarding certain tissue types can be expected to better retain DNA concentrations after boiling.